Paralisia cerebral e o atendimento terapêutico ocupacional domiciliar segundo rotta - de Oliveira Montagner, Liliane Doimo; Domingues, Loana Vieira; Gonzaga Maciel, Marnie Grubert (Multitemas, 2016)
__